2008
DOI: 10.1007/s10886-008-9427-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Three Pheromone Races of the Scarab Beetle Phyllophaga anxia (LeConte)

Abstract: This study offers experimental evidence for the existence of three pheromone races of the northern genitalic form of Phyllophaga anxia: one race in which females produce and males respond mainly to L-valine methyl ester, a second producing and responding to L-isoleucine methyl ester, and a third producing and responding to an intermediate range of blends of the two compounds. At Franklinville, NY, pheromone gland contents of females were analyzed using coupled gas chromatography-electroantennogram detection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…More than 60% of the captured males were later recaptured (Fig. 3), which is a much higher recapture rate than normally observed in mark-release-recapture studies using pheromone traps (Robbins et al 2008;Kishita et al 2003;Ö strand et al 2000; but see Zhang and Schlyter 1996).…”
Section: Discussionmentioning
confidence: 78%
“…More than 60% of the captured males were later recaptured (Fig. 3), which is a much higher recapture rate than normally observed in mark-release-recapture studies using pheromone traps (Robbins et al 2008;Kishita et al 2003;Ö strand et al 2000; but see Zhang and Schlyter 1996).…”
Section: Discussionmentioning
confidence: 78%
“…Assortative mating within strains of the same insect species with different pheromone components, or different ratios of those pheromone components, has also been described (Zhu et al 1997, Pélozuelo et al 2004, Pélozuelo et al 2007). Environmental factors can have a large influence on changes in pheromone-based communication systems (Svensson et al 2002, Yang and Du 2003, Pélozuelo et al 2004, Robbins et al 2008). It is possible, through differing selection pressures or genetic drift, that populations of P. xylostella maintained over many generations in laboratory or factory-rearing conditions could develop distinct behaviors or characteristics that would affect their interactions with wild individuals in an open-field setting or their ability to be monitored by pheromone lures.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, sex pheromone communication systems in moths have been assumed to involve strong stabilizing selection on emitters and receivers, and such stabilizing pressure would allow only small, incremental changes in pheromone systems over time (Paterson 1980). However, more recent investigations have revealed that many environmental factors can cause notable changes in these systems (Krokos et al 2002;Svensson et al 2002;Bashir et al 2003;Jun et al 2003;Yang and Du 2003;Pelozuelo et al 2004;Nosil et al 2007;Robbins et al 2008), and assortative mating can occur between different strains of the same insect species with different pheromone components or different ratios among components (Zhu et al 1997;Pelozuelo et al 2004).…”
Section: Introductionmentioning
confidence: 99%